A practical introduction to the thoracic ultrasonography of sheep. (2nd July 2020) - Evans, Mike; Hinde, Davinia; Scott, Phil
Abstract : Respiratory disease is common in sheep and thoracic ultrasonography can be a useful point of care diagnostic. This article describes how to perform thoracic ultrasonography in sheep, and provides examples of the lesions that may be identified, alongside practical advice gained through field experience. Ultrasonography should be combined with necropsy to confirm a proportion of diagnoses and build confidence using the technique in practice.